2020
DOI: 10.1016/j.rmcr.2020.101197
|View full text |Cite
|
Sign up to set email alerts
|

A case of large-cell lung carcinoma successfully treated with pembrolizumab but complicated with cholangitis

Abstract: Large-cell carcinoma (LCC) of the lung is defined as an undifferentiated non-small cell lung cancer (NSCLC) and accounts for approximately 7.5% of lung cancers. Immune checkpoint inhibitors (ICIs) may be effective for LCC, but there has been no firm evidence due to its low frequency. We herein report an 80-year-old woman with LCC of the lung who was successfully treated with pembrolizumab but developed sclerosing cholangitis as an immune-related adverse event. This case highlights the efficacy of ICIs for LCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the basis of real-world experience of IMH from the UK, prednisolone higher than 60 mg/day has not demonstrated any additional benefit regarding time to hepatitis resolution [28]. Therefore, if no inflammation remains in a repeated biopsy, tapering of GC is recommended [58].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of real-world experience of IMH from the UK, prednisolone higher than 60 mg/day has not demonstrated any additional benefit regarding time to hepatitis resolution [28]. Therefore, if no inflammation remains in a repeated biopsy, tapering of GC is recommended [58].…”
Section: Discussionmentioning
confidence: 99%
“…ICIs targeting PD‐L1 have been shown to be effective against multiple cancer types, including NSCLC 4 . Recently, there have been reports that ICI treatment is effective against rare histological types of NSCLC where PD‐L1 is highly expressed 6–8 . This case report suggests the possibility of a new treatment strategy for LCC, which is generally thought to have a poor prognosis.…”
Section: Discussionmentioning
confidence: 81%
“…The results of the KEYNOTE‐024 trial and KEYNOTE‐042 trials showed that pembrolizumab, a monoclonal antibody against PD‐1, was more effective than conventional platinum‐based combination chemotherapy as a first‐line treatment for advanced NSCLC expressing PD‐L1 on the tumor cells, which are negative for epidermal growth factor receptor gene (EGFR) mutation and anaplastic lymphoma kinase gene ( ALK ) rearrangement 4,5 . Furthermore, PD‐L1 inhibitors have been reported to be effective in rare classifications of NSCLC, such as LCC and pleomorphic carcinoma 6–8 …”
Section: Discussionmentioning
confidence: 99%
“…However, in the case reported by Ooi R et al., after the initial 1 mg/kg/day PSL treatment, IRH recurred during steroid reduction, and AZA was ineffective, although in this case after three days of pulse treatment with 1000 mg mPSL, "So-called" steroid-refractory IRH was successfully treated. This patient remained free of recurrence of the primary disease one year after ICI withdrawal as well [51] . The above case suggests that it is necessary to consider the use of steroid pulse therapy before diagnosing steroid-refractory IRH, and the steroid pulse therapy may not affect the prognosis of patients with tumor treatment.…”
Section: Steroid Refractoriness or Dose Of Steroid Is Not Enough?mentioning
confidence: 76%